Psychosocial Rehabilitation: The Community Re-Entry Program (CREP) in Psychiatric Inpatient Settings, Systematic Review - Dias, Carlos Manuel de Melo (2015)
Aim: This review is an update on the research evidence supporting psychosocial rehabilitation - the Community Re-Entry Program (CREP) in psychiatric inpatient settings. Method: This review is guided by the following questions: Is the Community Re-Entry Program (CREP) effective in psychiatric inpatient settings? and What are the main results and benefits of using this program in this patient population? Search strategy on Databases= MEDLINE and CINAHL (EBSCO), Cochrane Library, and SciELO, with no restriction on publication date and with the following keywords: Community Re-Entry Program OR CREP AND inpatients, in full text, in consecutive studies conducted between February, 2013, and October, 2014, in order to find all studies published that had used this program. Results: Results show that Patients with Experience of Mental Illness (PEMI) in the community re-entry program significantly improved their knowledge and performance of the skills taught in the sessions, compared to other patients. Community re-entry participants were also significantly more likely to attend their first aftercare appointment than other participants. Conclusions: The findings of the study clearly demonstrate the effectiveness of the CREP for clinical practice in psychiatric inpatient settings. From the patients' perspective, quality of life is enhanced. By learning skills to achieve their own personal relevant goals in life, individuals with serious mental disorders are empowered to function more autonomously from mental health professionals. Our general conclusion is that the Community Re-Entry Program for psychiatric inpatients is effective in teaching them about their illness and symptoms as well as improving their ability to make and keep appointments. Further studies should address the dissemination of the CREP in European countries, including a Portuguese Nursing version, as a way to increase the likelihood that the individual will be successful with skills training within the treatment and care areas of psychiatric and mental health nurses.